Wirausaha Frozen Food Rumahan Untuk Ketahanan Keluarga Pasca Covid 19 - Anwar Basalamah; Sri Fajar Ayuningsih; Ahmad Junaedi Abas Abas; Timotius Agus Rachmat Rachmat; Fitri Abdillah Abdillah; Asep Syaiful Bahri Asep Syaiful Bahri (Prisani Cendekia, 2023)
Changes in behaviour and lifestyle during the Covid-19 pandemic have resulted in a greater demand for ready-to-eat food that lasts a long time, making this a great opportunity right now. Furthermore, the flexibility to offer food products can be done in a variety of ways, from selling door-to-door, selling in canteens, restaurants, and restaurants, to selling online through digital platforms (social media and marketplaces). This expands the possibilities for a home-based frozen food business that can be run by housewives. The goal of this Community Service program with PKK member is to support capacity building for housewives to fill in more productive time, which can support providing additional family income. The target partner is homewifes as member of PKK at Perumnas 1, RW 007, Cibodasari Village, Cibodas District, Tangerang City. The research methodology associated with the strategy used in this activity includes (1) basic entrepreneurial knowledge, (2) debriefing materials on home-scale frozen food business opportunities, (3) material regarding the importance of food safety aspects for processed frozen food products, (4) demonstration of making simple frozen food, and (5) discussion and exploration of frozen food product ideas. As a result of this activity, housewives have more self-confidence and are more likely to start their own home culinary business. 30% of training participants have decided to start a home-based culinary business. The majority of participants were encouraged to accept frozen food orders and market them via social media.